MODERN AREAS OF DEVELOPMENT OF RESOURCE-BASED THEORY - O. Miroshnychenko; K. Kryvko (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
The essence of resource-based view is focus on using unique and rare combination of resources, core competences and organizational capabilities of the firm. The new intellectual resources and their combination provide the formation of sustainable competitive advantages. Therefore, it seems there is necessity to join in research the application of resource-based theory to creation of new combination of resources in dynamic environment. In this paper modern areas of development of resource-based theory have been considered. The concept of knowledge management, the concept of open innovation, the resource-based view and the system organization of economy have been characterised.